Cholesterol Induces Epithelial-to-Mesenchymal Transition of Prostate Cancer Cells by Suppressing Degradation of EGFR through APMAP - Jiang, Siyuan; Wang, Xuetong; Song, Dalong; Liu, XiaoJun; Gu, Yinmin; Xu, Zhiyuan; Wang, Xiaodong; Zhang, Xiaolu; Ye, Qinong; Tong, Zhou; Yan, BingXue; Yu, Jie; et al. (Cancer research (Chicago, Ill.), 2019)
Cholesterol increases the risk of aggressive prostate cancer and has emerged as a potential therapeutic target for prostate cancer. The functional roles of cholesterol in prostate cancer metastasis are not fully understood. Here, we found that cholesterol induces the epithelial-to-mesenchymal transition (EMT) through extracellular-regulated protein kinases 1/2 pathway activation, which is mediated by EGFR and adipocyte plasma membrane-associated protein (APMAP) accumulation in cholesterol-induced lipid rafts. Mechanistically, APMAP increases the interaction with EGFR substrate 15-related protein (EPS15R) to inhibit the endocytosis of EGFR by cholesterol, thus promoting cholesterol-induced EMT. Both the mRNA and protein levels of APMAP are upregulated in clinical prostate cancer samples. Together, these findings shed light onto an APMAP/EPS15R/EGFR axis that mediates cholesterol-induced EMT of prostate cancer cells. SIGNIFICANCE: This study delineates the molecular mechanisms by which cholesterol increases prostate cancer progression and demonstrates that the binding of cholesterol-induced APMAP with EPS15R inhibits EGFR internalization and activates ERK1/2 to promote EMT. GRAPHICAL ABSTRACT: http://cancerres.aacrjournals.org/content/canres/79/12/3063/F1.large.jpg.